Children in the 21st Century: A Brief Overview of Children’s Mental Health Issues and Psychological Well-Being in Contemporary Society - Žulec Ivanković, Ana; Selak, Matea Bodrožić; Merkaš, Marina (Social and Personality Development in Childhood, 2025)
In the 21st century, children face a unique set of challenges that were inconceivable a few decades earlier. Daily, children confront heightened stress from social pressures, academic demands, and the pervasive digital environment. The changing dynamics of family functioning, peer relationships, and cultural influences might be challenging for children’s well-being and mental health. Recent studies show a significant rise in mental health issues among children in the 21st century. Before we outline how the society can help, it is important to gain some understanding of mental health issues. First, we define mental health issues, and second, we explain how mental health issues arise and develop, and which factors make children vulnerable to the development of mental health issues; third, we provide a detailed overview of the prevalence of the most common mental health issues in children and adolescents. Finally, some strategies that might contribute to the protection of children in the modern era are presented. Keywords: children, mental health issues, psychological well-being, risk and protective factors, prevention